Pola Pikir Remaja Dilihat dari Konten Tiktok dan Intensitas Penggunaan Tiktok dengan Gaya Hidup sebagai Variabel Mediasi - Syarofi , Ahmad Muhtar (Future Science, 2024)
This study explores the impact of TikTok content and its usage intensity on adolescents' mindsets, with digital lifestyle serving as a mediating variable. TikTok, as a leading social media platform, offers diverse con-tent that can influence adolescents' perspectives and behaviors. This re-search employs a quantitative approach using PLS-SEM to analyze the relationships among independent variables (TikTok content and usage intensity), the mediating variable (digital lifestyle), and the dependent variable (adolescents' mindsets). The findings indicate that TikTok con-tent and its usage intensity have direct effects on adolescents' mindsets, both positive and negative, depending on the type of content and usage duration. Additionally, digital lifestyle is shown to be a significant medi-ating factor. This study emphasizes the importance of digital literacy in enabling adolescents to filter information and use social media wisely, thereby fostering healthy and constructive mindsets.